Pengalaman Self Disclosure Wanita yang Menikah Muda Dalam Membangun Komitmen Selama Menjalankan Proses Ta’aruf - Nabila Noerfadjria; Yulianti (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Marriage is a commitment in believing that a relationship is a lifelong relationship, and believing that the chosen partner is the right choice. In Islam, before a pair of individuals establishes themselves to do marriage, there are stages known as Ta'aruf. The time period is quite short, the interaction is limited and there is no space and time to be alone between the two parties before the marriage contract is signed, and can lead to a lack of openness between the prospective husband or wife. The less the adjustment process, the less likely it is to build commitment. Therefore, the research wants to explain how each individual interacts with each other and opens themself so that they can build commitment to marry at a young age through the Ta'aruf process. The purpose of this research is to find out their experiences of Self Disclosure during the Ta'aruf process. The two main focuses are viewed from the experience of the subject as an